The Saprophytic Lifestyle of Listeria monocytogenes and Entry Into the Food-Processing Environment - Lourenco, Antonio; Linke, Kristina; Wagner, Martin; Stessl, Beatrix (Frontiers in Microbiology, 2022)
Listeria monocytogenes is a highly environmentally adapted saprophyte that can change into a human bacterial pathogen with zoonotic potential through the σB and PrfA regulatory systems. In this review, the focus is on the occurrence of Listeria sensu stricto and sensu lato in different ecological niches, the detection methods and their analytical limitations. It also highlights the occurrence of L. monocytogenes genotypes in the environment (soil, water, wildlife), reflects on the molecular determinants of L. monocytogenes for the saprophytic lifestyle and the potential for antibiotic resistance. In particular, the strain-specific properties with which some genotypes circulate in wastewater, surface water, soil, wildlife, and agricultural environments is of particular interest for the continuously updating risk analysis.